Can power and anaerobic capacity reduce according to disordered eating behaviors in cyclists? - Leonardo de Sousa Fortes; Lilyan Carla Vaz Mendonça; Pedro Pinheiro Paes; Jeferson Macedo Vianna; Fernando Diefenthaeler
Abstract The present study aimed to compare the power, anaerobic capacity (AC) and performance in a road bicycle race among cyclists with and without risk of disordered eating behaviors (DEB). The sample was selected in a non-probabilistic way, totaling 69 male road cyclists aged between 19 and 30 years. The Wingate test was used to evaluate peak power (PP) and mean power. Time in minutes was adopted to determine performance in a 120-km road cycling race (competitive event). The Eating Attitudes Test (EAT-26) was completed to assess DEBs. The results did not indicate a difference in PP among cyclists with and without risk of DEBs (F (2, 67)=3.92; p=0.13). Findings showed a difference in mean power among cyclists with and without risk of DEBs (F (2, 67)=36.43; p=0.01). The results revealed a difference in performance in 120-km cycling races among cyclists with and without risk of DEBs (F (2, 67)=46.03; p=0.01). It could be concluded that DEBs were associated with a lower mean power and performance in a competitive event among male road cyclists, although the same was not true for PP.